Optimalisasi Pelayanan Publik di Nagari Sontang Cubadak Kecamatan Padang Gelugur Kabupaten Pasaman - Anwar, Ismail; Malau, Hasbullah (PUBLICNESS: Journal of Public Administration Studies, 2025)
This study is to describe the optimization of public services in Nagari Sontang Cubadak, Padang Gelugur District, Pasaman Regency. The background of this study is because there are still many people who experience obstacles when accessing services in Nagari Sontang Cubadak. The purpose of this study is to determine the optimization of public services in Nagari Sontang Cubadak and to determine the inhibiting factors for optimizing public services in Nagari Sontang Cubadak. The research method used is a qualitative approach using a descriptive method. Informants in this study were selected using purposive sampling techniques. This study uses data collection techniques in the form of observation, interviews and documentation. This study uses the Hotniar Siringo-ringo theory which focuses on optimization of objectives, alternative decisions, and limited resources. The village government has made three alternative decisions, namely improving the skills and training of officers, providing information boards, and weekly evaluations. However, these three alternative decisions have not been able to overcome the service problems in Nagari Sontang Cubadak as a whole. Factors Inhibiting Service Optimization include limited human resources, limited budget, lack of socialization and information regarding service procedures, lack of training for officers, and low participation in providing input on services.